Determinación global y salud: el marco amplio de los determinantes de la salud (2013)
ABSTRACT: The purpose of this essay is to present the challenges faced by global health during the last stage of the development of global capitalism and its relationship with the social and sanitary determinants of health, life and earth based on a new concept: global determination. Methodologically, the following subjects are developed: global determination and its relationship with the social determinants of health, the consequences of global capitalism, the challenges faced by humanity and by global health, and the issue of governance and global social response. Likewise, the globalization of capitalism is discussed as the main determinant for governmental action, as well as for social and public health policies along with their consequences: the threat of war, the economic crisis, hunger, the degradation of the biosphere, ethnic displacements, etc. Similarly, the author defends the idea of facing the deterioration of living conditions and the increase of social inequalities. The great challenge that explains the other issues in global health is indeed social inequities, since they are the cause of poor health and health inequalities. Such inequities appear for reasons related to geography, age, gender, ethnicity, educational level, and income distribution, yet they ultimately arise from social determinants that are born in the supranational domain of determination. In the conclusions, the author defends global action as a way to overcome the inequalities and inequities affecting today’s world, and proposes a new category to understand social determinants: the global determination, which has a greater explanatory power compared to the various theoretical currents discussing determinants and social determination.